Outline of Competency-Based Assessment in a Course Designed under the Model of Competency-Based Education - Guillén Mujica, Alejandro (2022)
The philosophy of Competency-Based Education burst forth with great force when planning university programs. The Faculty of Engineering of the Central University of Venezuela was the first in Venezuela to embrace this philosophy when it created the Industrial Process Engineering major in 2008. The programs were designed with their competency indicators, without specifying an adequate plan to evaluate them, as it happens in the Organizational Development course. The scheme developed in this research project, in the first place weighs, according to their importance, the topics contained in the course and establishes the required assessment instruments. Later, each evaluation technique is associated with a competency and complements it with an evaluation template and a list of actions, in which each achievement is expressed. All these data were finally downloaded into an individualized form through which the participant can recognize their qualification and performance. The research is methodologically based on the interpretative-phenomenological paradigm, appropriate for research in the educational area, with a qualitative approach supported by literature review. The model seeks to support the teacher, by giving him or her a new way to evaluate competences since this is easier to implement and use.